Employee Performance in the Digital Era: The Role of Transformational Leadership and Employee Involvement - Muhammad Salman Al-Farisi; Ade Solahudin (Institute of Computer Science (IOCS), 2026)
The implementation of the Electronic-Based Government System (SPBE) has intensified the need for public organizations to strengthen employee performance through digital adaptation and effective leadership practices. However, limited studies have examined the mediating role of employee engagement in linking digital transformation and transformational leadership to employee performance within public sector institutions. This study investigates the direct and indirect effects of digital transformation and transformational leadership on employee performance through employee engagement at the Ministry of Religious Affairs of Majalengka Regency. This research employed a quantitative associative approach using a survey method. Data were collected from 180 employees selected through simple random sampling using structured questionnaires with Likert-scale measurements. The data were analyzed using path analysis and the Sobel test with SPSS version 22 to evaluate the mediation effect. The findings indicate that digital transformation and transformational leadership have positive and significant effects on employee engagement and employee performance. Employee engagement also significantly improves employee performance and partially mediates the relationship between digital transformation and performance, as well as transformational leadership and performance. Furthermore, Digital Transformation, Transformational Leadership, and Employee Engagement jointly explain 87.1% of the variance in employee performance (Adjusted R² = 0.871). These findings demonstrate that employee engagement plays a strategic mediating role in strengthening employee performance during digital transformation in public sector organizations. The study contributes to the public management and organizational behavior literature by integrating digital transformation, transformational leadership, and employee engagement into a unified performance model within the government sector